2013
DOI: 10.3892/mmr.2013.1386
|View full text |Cite
|
Sign up to set email alerts
|

Developmental delay referrals and the roles of Fragile X testing and molecular karyotyping: A New Zealand perspective

Abstract: Global developmental delay (GDD) affects ~1-3% of children, many of whom will also have intellectual disability (ID). Fragile X is the major genetic cause of GDD with mental retardation (MR) in males, accounting for ~20% of all X-linked MR. As Fragile X has serious genetic implications, the overwhelming majority of developmental delay (DD) cases referred to our laboratory are concerned with the exclusion of a diagnosis of Fragile X, along with simultaneous karyotype analysis to confirm chromosome aberrations. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 18 publications
0
2
0
1
Order By: Relevance
“…However, nearly all individuals with an ID also have documented developmental delays [Doherty et al, 2013] and only a small proportion of the cohort had ID/DD but no major physical congenital anomalies. Also, we found that a diagnosis of ID/DD for any subgroup (pediatric to adult), did not shorten time to diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…However, nearly all individuals with an ID also have documented developmental delays [Doherty et al, 2013] and only a small proportion of the cohort had ID/DD but no major physical congenital anomalies. Also, we found that a diagnosis of ID/DD for any subgroup (pediatric to adult), did not shorten time to diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…The MRI scan of his brain was unremarkable and his creatinine kinase level was 35 U/L (normal age-specific range 30–150) [18]. Fragile X testing involved PCR amplification and then fluorescence-based capillary electrophoresis to determine the number of CGG repeats within the FMR-1 gene [19]. He was found to have a normal CGG repeat length of 30.…”
Section: Case Reportmentioning
confidence: 99%
“…Με τη CMA μεθοδολογία, σε ασθενείς με νευροαναπτυξιακές ασθένειες, είναι δυνατό να εντοπιστούν διαγνωστικά ευρήματα σε ποσοστό 1520% 140; 142; 143 . Σε 19 μελέτες που αναφέρουν τη διαγνωστική ικανότητα του CMA και περιλαμβάνουν περισσότερα από 150 άτομα με νοητική και αναπτυξιακή καθυστέρηση, η διαγνωστική ικανότητα βρέθηκε να κυμαίνεται από 4.5-28% (κατά μέσο όρο 13.7%) [144][145][146][147][148][149][150][151][152][153][154][155][156][157][158][159][160][161][162] . Επίσης, σε 11 μελέτες που περιλαμβάνουν ασθενείς του αυτιστικού φάσματος (κάθε μελέτη περιλάμβανε τουλάχιστον 50 άτομα), η τεχνολογία CMA ανίχνευσε διαγνωστικά μοριακά ευρήματα σε 1.5 ως 20.5% (κατά μέσο όρο 8.1%) 149; 151; 152; 157; 162-168 .…”
Section: η τεχνολογία Chromosomal Microarray (Cma) « μοριακός καρυότυπος»unclassified